Amyotrophic lateral sclerosis in seven provinces of Chinese mainland: A cross-sectional survey from 2015 to 2016 - Zhang, Jie; Liu, Xiaoqing; Liang, Huiting; Xu, Shengyuan; Wang, Xiaohua; Xu, Renshi (Frontiers in Aging Neuroscience, 2022)
Background: The large-scale survey about amyotrophic lateral sclerosis (ALS) based on both population and hospital in the Chinese mainland has been deficient at present. To this end, we conducted a cross sectional survey about ALS based on population and hospital in 7 provinces of Chinese mainland in 2015-2016. Methods: We surveyed ALS patients of 7 provinces in the eastern, middle and western China. Among them, 13 prefecture-level cities, 13 municipal districts and 13 counties, 26 streets, 52 communities, 39 towns and 78 administrative villages were selected for the population-based survey. 13 class-3 general hospitals, 13 class-2 general hospitals and 26 street health centers or community health service centers in urban districts, and 13 county-level general hospitals, 39 township health centers and 78 village clinics in rural districts were recruited for the hospital-based survey. Results: Among the Chinese mainland, total prevalence of ALS was slightly lower than that of the world other nations or districts. The male patients were more than the female patients. The prevalence of rural residents was more than that of urban residents. The prevalence of farmer was higher than that of other professions. Majority of ALS weren't accompanied by other chronic diseases. The peak onset age of ALS was higher, familial ALS (fALS) cases were slightly more and the average survival duration of sporadic ALS (sALS) was slightly lower compared with the previous investigation data. The hospitalization expenses of almost 60% ALS weren’t more than 10,000 Chinese Yuan. Conclusion: Hospitalization expenses in our survey objectives were the lowest in the current reported countries and districts. Farmer was a possible higher risk profession of ALS, the majority of ALS weren't accompanied by other chronic diseases. Our survey provided more information for the epidemiology of ALS in the worldwide, and supplied the deficiency of epidemiology survey about ALS from the Chine mainland.